Recent developments in the synthesis of nanomaterials in the combustion regime - Mansurov, Z.A. (Recent Contributions to Physics, 2012)
Proposed scheme of conversion of fuel with the formation of fullerenes and carbon black taking into account the pressure in the fuel-rich flames. It is shown that the formation of fullerenes is important to the corresponding spatial orientation PAH, possible at low pressures. Investigated the influence of an electric discharge on the efficiency of output of fullerenes in premixed benzene / oxygen / argon flame. It is established that the electrons emitted from the needle electrode, distributed in the volume of a cone, and to a lesser degree of influence on the outer edges of the flame, and the electrons emitted from the annular electrode is treated not only the inner region, but also the edge of the flame, which creates conditions for growth fullerenes. Studied the formation of hydrophobic soot in the diffusion of propane – oxygen flame on the silicon and nickel substrates at atmospheric pressure and defined conditions for the formation of superhydrophobic carbon black on a nickel substrate from exposure to electric fields. It is established that the imposition of an electric field, regardless of the substrate material, deposition of soot narrows the field to the substrate, and a diameter of 2.5 – 3 cm from the center formed a diesel particulate superhydrophobic surface with wetting angle from above 1700. Synthesis of carbon nanotubes carried out on microwave plasma-chemical reactor. The resulting nanotubes were studied by electron microscope and SEM – images of films of carbon nanotubes shows that the nanotubes are randomly distributed on the substrate and disoriented. It was found that the growth rate depends on the amount of methane suppressed. Studied the photovoltaic properties of solar cells coated with nickel oxide nanoparticles synthesized in counterflow propane flame. Nanoparticles of nickel oxides contribute to the efficient absorption of light energy. Surfacing on the surface of a silicon solar cell of nickel oxide nanoparticles led to an increase in the output circuit voltage up to 4-7%, short circuit current up to 20-28%, which together led to an increase in solar cell efficiency by 2-3%.